2014
DOI: 10.1002/eat.22244
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of healthy living blogs: Evidence of content thematically consistent with dysfunctional eating attitudes and behaviors

Abstract: These findings suggest the content of healthy living blogs might be problematic for viewers who have eating or body image issues. The content does not approach the inflammatory nature of pro-eating disorder websites, yet information promoted clearly indicates that future research should further evaluate these sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 24 publications
(47 reference statements)
4
53
0
3
Order By: Relevance
“…The issues of frustration, guilt and feeling addicted to viewing Fitspirational posts are novel insights emerging from the current study. Negative effects of exposure to Fitspiration on self-esteem, body image and disordered eating have been demonstrated [3] and speculated upon [7][8][9][10][11][12][13] previously and the accounts of our participants are in line with these studies and also the proposition that social comparison on the basis of appearance is one of the routes by which Fitspiration produces negative psychological effects [3].…”
Section: Discussion Key Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…The issues of frustration, guilt and feeling addicted to viewing Fitspirational posts are novel insights emerging from the current study. Negative effects of exposure to Fitspiration on self-esteem, body image and disordered eating have been demonstrated [3] and speculated upon [7][8][9][10][11][12][13] previously and the accounts of our participants are in line with these studies and also the proposition that social comparison on the basis of appearance is one of the routes by which Fitspiration produces negative psychological effects [3].…”
Section: Discussion Key Findingssupporting
confidence: 85%
“…Concern has also been raised about the posters of Fitspirational material, with one study showing that women who post Fitspirational content have more maladaptive eating and body image problems than control women [12]. A content analysis of Fitspirational blogs (in which people write about their experiences of living a healthier lifestyle) found evidence of problematic eating, negative attitudes towards food and body image [13].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of health information on social media varies widely; one study found that about half of “healthy living” blogs contained negative and stigmatizing messages about food or weight (18). Because of high rates of social media use among adolescents and young adults, concern is increasing about the promotion of disordered eating behaviors among online communities (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…A related and similarly concerning media trend is that the current ideal feminine body is not only very thin, but also exceedingly fit (Boepple & Thompson, 2014;Thompson, van Den Berg, Roehrig, Guarda, & Heinberg, 2004). Young adult women increasingly report a preference for broad shoulders and muscular arms (Thompson et al, 2004).…”
mentioning
confidence: 99%